Diarrhea Prevention Counseling for Grade 4 and 5 School Students - Ristiana, Niken; Cahaya kusuma, Nur; Nurlinawati, Nurlinawati (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Diarrhea is a disease which if not treated properly can cause sudden loss of fluids and electrolytes, so that various complications can occur including dehydration, hypovolemic shock, organ damage and even coma. The most severe threat posed by diarrhea is dehydration which can lead to death, therefore the incidence of diarrhea is a health problem whose occurrence needs to be suppressed. The type of research used in this research is